Finding a Needle in a Haystack: Identification of EGFP Tagged Neurons during Calcium Imaging by Means of Two-Photon Spectral Separation - Brondi, Marco; Sulis Sato, Sebastian; Rossi, Luigi Federico; Ferrara, Silvia; Ratto, Gian Michele (Frontiers in Molecular Neuroscience, 2012)
The combination of two-photon in vivo imaging and genetic labeling of specific cell types in the mouse brain is a powerful method to refine our understanding of brain circuitry and to dissect the contribution of specific neural classes to cortical function. The synthetic calcium indicators are the best fluorescent reporters for cellular activity that are presently available but their spectral proprieties are often overlapped with those of the fluorescent proteins used for genetic labeling. Such is the case of Oregon Green BAPTA1 and EGFP, the most widely used fluorophores for targeted two photon imaging. The emission spectra of these molecules are virtually identical, precluding their separation by narrow band filters at the detector side. However, even if their one-photon excitation spectra are very similar, their two-photon excitation spectra differ significantly: here we show how it is possible to exploit this difference to separate the relative contributions of EGFP and Oregon Green to the total fluorescence signal. This approach addresses two different issues: the unbiased detection of cells expressing EGFP in a cortical volume injected with Oregon Green, and the computation of the Ca2+ insensitive fluorescence background. The latter data is essential for the quantitative comparison of the relative changes in Ca2+ concentration between different cells, containing variable concentrations of EGFP. This strategy can be easily extended to any couple of fluorophores provided that have a different two-photon excitation spectra.